2022
DOI: 10.3389/fendo.2022.842421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Regulator of G Protein Signaling Proteins on Bone

Abstract: Regulator of G protein signaling (RGS) proteins are critical negative molecules of G protein-coupled receptor (GPCR) signaling, which mediates a variety of biological processes in bone homeostasis and diseases. The RGS proteins are divided into nine subfamilies with a conserved RGS domain which plays an important role in regulating the GTPase activity. Mutations of some RGS proteins change bone development and/or metabolism, causing osteopathy. In this review, we summarize the recent findings of RGS proteins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 62 publications
(96 reference statements)
0
10
0
Order By: Relevance
“…Su Yin Lim et al found that CCL2-CCR2 signaling is a key process in cancer metastasis 43 . G protein-coupled receptor (GPCR) and regulators of G protein signaling (RGS) family proteins are involved in a variety of diseases such as cancer, arthritis, metabolic dysfunctions, and aging-related diseases [44][45][46][47][48][49][50][51][52][53][54][55][56] . Wendy Kleibeuker et al found that physiological changes of G protein-coupled receptor kinase 2 (GRK2) control CCL2-induced signaling 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Su Yin Lim et al found that CCL2-CCR2 signaling is a key process in cancer metastasis 43 . G protein-coupled receptor (GPCR) and regulators of G protein signaling (RGS) family proteins are involved in a variety of diseases such as cancer, arthritis, metabolic dysfunctions, and aging-related diseases [44][45][46][47][48][49][50][51][52][53][54][55][56] . Wendy Kleibeuker et al found that physiological changes of G protein-coupled receptor kinase 2 (GRK2) control CCL2-induced signaling 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Andre Luiz Prezotto Villa et al reported that the PPARG expression is related to cancer stages and clinical evolution 39 . G protein-coupled receptors are widely expressed in cells and their downstream signaling pathways are involved in a number of pathological processes [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] Our study identi ed the potential vital molecules and signaling pathways related to the LDHA-mediated PDAC. This study showed that TNF signaling pathway and Cellular senescence are the major processes during the LDHA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Z Huang et al found that CDK1 increases the interaction of SOX2 to further enhance the stemness of lung cancer cells 15 . G protein-coupled receptors are essential for cell functions and are involved in several diseases [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] . P M Cobelens et al found that hydrogen peroxide damages GRK2 (GPCRrelated protein) via calpain and cdk1-mediated signaling pathway 35 .…”
Section: Discussionmentioning
confidence: 99%